PEMBELAJARAN BERDEFERENSIASI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI KELAS 5 SEKOLAH DASAR - Hajar Hanifah, Habila; Muhroji (Universitas Negeri Medan, 2025)
Abstract: The research objectives are 1.) Describe the implementation of differentiated learning at Muhammadiyah Nurul Ilmi Elementary School. 2.) Describe the impact of differentiated learning in improving the quality of learning at Muhammadiyah Nurul Ilmi Elementary School. 3.) Describe the factors inhibiting the implementation of differentiated learning at SD Muahammadiyah Nururl Ilmi. This research is descriptive qualitative. The research subjects were the Principal, Deputy Head of Curriculum, Teachers, and students. Data collection techniques used observation, interviews and documentation. Data analysis includes interactive data reduction, data presentation, and drawing conclusions. The research results showed that 1.) The implementation of differentiated learning at SD Muhammadiyah Nurul Ilmi has been implemented with three differentiation strategies, namely content differentiation, process differentiation and product differentiation. 2.) Impact on the quality of learning. 3.) Factors inhibiting the implementation of differentiated learning. Keyword: Differentiated Learning, Merdeka Curriculum, Elementary School Abstrak: Tujuan penelitian yaitu 1.) Mendeskripsikan implementasi pembelajaran berdiferensiasi di SD Muhammadiyah Nurul Ilmi. 2.) Mendekripsikan dampak pembelajaran berdeferensiasi dalam meningkatkan kualitas pembelajaran di SD Muhammadiyah Nurul Ilmi. 3.) Mendeskripsikan faktor-faktor penghambat implementasi pembelajaran berdiferensiasi di SD Muahammadiyah Nururl Ilmi. Penelitian termasuk deskriptif kualitatif. Subjek penelitian adalah Kepala Sekolah, Waka Kurikulum, Guru kelas, dan siswa. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Analisis data interaktif meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Pada penelitian didapatkan hasil bahwa 1.) Implementasi pembelajaran berdiferensiasi di SD Muhammadiyah Nurul Ilmi telah diterapkan dengan tiga strategi diferensiasi yaitu diferensiasi konten, diferensiasi proses, dan diferensiasi produk. 2.) Dampak terhadap kualitas pembelajaran. 3.) Faktor penghambat penerapan pembelajaran berdiferensiasi. Kata Kunci: Pembelajaran Berdeferensiasi, Kurikulum Merdeka, Sekolah Dasar